2003
DOI: 10.1002/ange.200350949
|View full text |Cite
|
Sign up to set email alerts
|

The Dienyl Pauson–Khand Reaction

Abstract: Studies in our organometallic subgroup are aimed at the design and development of new catalytic reactions, with an emphasis on processes that, in the absence of catalysts, would be forbidden or would require harsh conditions. [1,2] These studies have thus far produced the first examples of transition-metal-catalyzed [4þ4] cycloadditions of bisdienes, [3] [4þ2] cycloadditions of dienynes (and diene allenes), [4] [5þ2] cycloadditions of vinylcyclopropanes and p systems, [5] and [6þ2] cycloadditions of vinylcyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 80 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…Toward this end, we have directed effort at the identification of new metal‐catalyzed reactions, especially those which are forbidden or difficult to achieve in the absence of a catalyst. This program has thus far produced several new two‐, three‐, and four‐component reactions, including [4+4],2 [4+2],3 [5+2],4 [6+2],5 [5+2+1],6 [2+2+1],7 [4+2+1],7a and [5+1+2+1]8 cycloadditions. Herein, we report the first examples of the [2+2+1] cycloaddition reaction of diene–allenes and CO and preliminary examples of acceleration of this process by Brønsted acids.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Toward this end, we have directed effort at the identification of new metal‐catalyzed reactions, especially those which are forbidden or difficult to achieve in the absence of a catalyst. This program has thus far produced several new two‐, three‐, and four‐component reactions, including [4+4],2 [4+2],3 [5+2],4 [6+2],5 [5+2+1],6 [2+2+1],7 [4+2+1],7a and [5+1+2+1]8 cycloadditions. Herein, we report the first examples of the [2+2+1] cycloaddition reaction of diene–allenes and CO and preliminary examples of acceleration of this process by Brønsted acids.…”
Section: Methodsmentioning
confidence: 99%
“…With CO as the trapping agent, this approach indeed proved effective, thus resulting in the first examples of an intramolecular dienyl Pauson–Khand reaction [Eq. (2)] and a new [4+2+1] cycloaddition (not shown) 7a. 10 Significantly, the diene was found to facilitate the reaction relative to an alkene [cf.…”
Section: Methodsmentioning
confidence: 99%
“…[30] Internal alkynes gave excellent yields of the PK cycloadducts (85Ϫ96% yield), whereas terminal alkynes reacted less efficiently. In view of the potential synthetic utility of this dienic version, Wender and co-workers focused their attention on the selectivity of the reaction of dienynes for the intramolecular [2ϩ2ϩ1] pathway.…”
Section: 3-dienic Pauson؊khand Reactionmentioning
confidence: 99%
“…[1] Our studies toward this objective have thus far resulted in new metal-catalyzed [4+4], [2] [4+2], [3] [5+2], [4] and [6+2] [5] cycloadditions and three-component [5+2+1], [6] [4+2+1], and [2+2+1] reactions. [7] In the course of our studies on the rhodium(i)catalyzed intramolecular dienyl [2+2+1] Pauson-Khand reaction, we observed that when a diene is used in place of an alkene the reaction rate is significantly accelerated. [7] The present study was aimed at determining whether this enhanced reactivity would enable the use of dienes in a catalyzed intermolecular [2+2+1] Pauson-Khand reaction.…”
mentioning
confidence: 99%
“…[7] In the course of our studies on the rhodium(i)catalyzed intramolecular dienyl [2+2+1] Pauson-Khand reaction, we observed that when a diene is used in place of an alkene the reaction rate is significantly accelerated. [7] The present study was aimed at determining whether this enhanced reactivity would enable the use of dienes in a catalyzed intermolecular [2+2+1] Pauson-Khand reaction.…”
mentioning
confidence: 99%